The Effect of Heat Exchanger Design on Heat Transfer Rate and Temperature Distribution - Saad S. Alrwashdeh; Handri Ammari; Mazen A. Madanat; Ala’a M. Al-Falahat (Emerging Science Journal, 2022)
The heat exchanger (HE) is a device that is used to complete the process of heat transfer between different matters without direct mixing. Therefore, it is of great importance in the transfer of energy and the completion of various energy transition processes. In the processes of HE between different energy systems, many factors influence and play a major and important role in the efficiency of transformation and exchange in forms of energy, such as the length, the material type, the exchange fluid, the surrounding environment, and many other factors. In this work, the effect of the HE length of the parallel and counter flow HEs was investigated based on the use of computer simulation programs. There was a significant impact of the exchange factors, especially the length of the HEs in both the parallel and counter-flow HEs, on the quality and efficiency of the HE and the temperature distribution. The overall evaluation shows that by increasing the length of the HE for both parallel and counter-flow HEs, the heat transfer is increased and the heat distribution becomes more homogeneous, which aids in enhancing the transfer of energy efficiency inside the HEs. Doi: 10.28991/ESJ-2022-06-01-010 Full Text: PDF